EDUKASI KESEHATAN DI MASA NEW NORMAL PADA ANAK - Ida Windi Wahyuni; Raihana Raihana; Dian Tri Utami; Ella Setiani; Syarifah Halimah Shafira (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The main purpose of this activity is that it is hoped that posyandu participants, orphanage residents, and students of the Harapan Bunda PAUD students in Kampar Kiri Hilir Subdistrict, Kampar Regency can understand and apply clean living behavior in entering the new normal. The target of dedication is 41 children. There is an increase in knowledge and understanding of the participants of Posyandu, Aulia Orphanage, and the Harapan Bunda PAUD regarding covid-19 and its symptoms, and parents/teachers/orphanages teachers remain as companions and mentors in applying health to themselves so they are not exposed to the covid-19 virus. Furthermore, the results of this activity are expected to increase the attitude and behavior of children to be more independent and able to understand the spread of the covid-19 virus and how to prevent it and to maintain distance, use masks, and always wash hands.